2020
DOI: 10.1039/d0ob00938e
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stimuli controlled release of a transmembrane chloride ion carrier from a sulfonium-linked procarrier

Abstract: In recent times, anion transporters have accomplished substantial consideration due to their ability to disrupt ionic equilibrium across the membrane bilayers. While numerous Cl─ ion transporters were developed for channelopathies,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…A literature search shows that egg yolk phosphatidylcholine (EYPC) and 2-oleoyl-1-palmitoyl-sn-glycero-3phosphocholine (POPC, Figure 5) are the most commonly used lipids; however, 1palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2oleoyl-sn-glycero-3-phosphoglycerol (POPG) have also been employed. For instance, Matile's, [21][22][23][24][25][26] Talukdar's, [27][28][29][30][31] and Ballester's 21,32 research groups have used EYPC from Avanti Polar Lipids, while Chen 33-37 and Manna [38][39] have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 14,17,20,[40][41][42][43] and Quesada As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked.…”
Section: Lipidsmentioning
confidence: 99%
“…A literature search shows that egg yolk phosphatidylcholine (EYPC) and 2-oleoyl-1-palmitoyl-sn-glycero-3phosphocholine (POPC, Figure 5) are the most commonly used lipids; however, 1palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2oleoyl-sn-glycero-3-phosphoglycerol (POPG) have also been employed. For instance, Matile's, [21][22][23][24][25][26] Talukdar's, [27][28][29][30][31] and Ballester's 21,32 research groups have used EYPC from Avanti Polar Lipids, while Chen 33-37 and Manna [38][39] have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 14,17,20,[40][41][42][43] and Quesada As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked.…”
Section: Lipidsmentioning
confidence: 99%
“…155 An example of the latter approach has been reported by Manna and co-workers, who showed that a water soluble and inactive sulfonium-based pre-anionophore could be made membrane permeable by reduction with glutathione, leading to activation of anion transport (Figure 18B). 150 Chloride transport could also be stimulated by reactive oxygen species or by irradiation with 365 nm light. Cancer cells over produce ROS and GSH thus this chloride specific carrier may be suited to applications within targeted cancer therapy.…”
Section: Stimuli-responsive Transport Systemsmentioning
confidence: 99%
“…A literature search shows that egg yolk phosphatidylcholine (EYPC) and 2-oleoyl-1-palmitoyl-sn-glycero-3phosphocholine (POPC, Figure 5) are the most commonly used lipids; however, 1palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2oleoyl-sn-glycero-3-phosphoglycerol (POPG) have also been employed. For instance, Matile's, [22][23][24][25][26][27] Talukdar's, [28][29][30][31][32] and Ballester's 22,33 research groups have used EYPC from Avanti Polar Lipids, while Chen [34][35][36][37][38] and Manna 39,40 have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 15,18,21,[41][42][43][44] and Quesada 45, As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked.…”
Section: Lipidsmentioning
confidence: 99%
“…16,21 Finally, it is important to note that sometimes a mixture of lipid and cholesterol has been prepared to carry out transport experiments due to the contribution of the latter to the stabilisation of the vesicles' membrane. 34,39,40,46 Their proportions may vary, but Quesada's group uses a 7:3 POPC:cholesterol mixture with good results.…”
Section: Lipidsmentioning
confidence: 99%